ANALYZING ENGLISH AND UZBEK MEDIA DISCOURSE LINGUISTICALLY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the course of its development, media linguistics gradually separated from a number of other sciences into a separate, special direction, which, with the help of resources of different languages is aimed at exploring the global spectrum of problems linguistics, among which is the formation of "media reality". This article analyses English and Uzbek media discourse linguistically.